Analisis Determinan Berat Badan Lahir Rendah (BBLR) Di Provinsi Nusa Tenggara Timur Tahun 2017 - Elina Mayasari; Geraldi Putra Prasetya Balebu; Latifah Hasanah; Rizka Wulandari; Rani Nooraeni (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2020)
Health is one of the essential needs for human beings, and even became a major issue that indicates achievement of a country or a region. Health can also be viewed from the condition of the infants, which can be measure from Infant Mortality Rate (IMR). This indicator shows a high rate especially because of low birthweight. The cases of low birthweight is one of the highest case that occurred in developing countries, including Indonesia. Nusa Tenggara Timur (NTT) province in Indonesia, is one of the most common places where this case is most likely to happened. The percentage of the low birthweight case is higher than the average case in Indonesia. Therefore, this research paper aim to investigate variables which are responsible for causing low birthweight case in such a high number in NTT on 2017. The method used for analysis is logistic regression. The result indicate that mother’s education level is significantly affecting low birthweight cases in NTT.